Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Kemampuan Menulis Teks Eksplanasi oleh Siswa Kelas VII di SMP Negeri 2 Tapian Dolok - Heru P. Sitorus; Jumaria Sirait; Monalisa Frince Sianturi (Medan Resource Center, 2022)
This study aims to determine: (1) the ability to write explanatory texts in class VIII students at SMP Negeri 2 Tapian Dolok before using Contextual Teaching and Learning (CTL) learning. (2) The ability to write explanatory texts for students of SMP Negeri 2 Tapian Dolok after the Contextual Teaching and Learning (CTL) model. (3) The effect of using the Contextual Teaching and Learning (CTL) learning model on the ability to write explanatory texts by class VIII students at SMP Negeri 2 Tapian Dolok. This research uses quantitative research. The method used is an experimental method while the method used in this research is Pre-Experimental Design (non-design). According to Sugiyono (2019:112) that the results of Pre-Experimental research are independent variables. This happened, because there were no control variables, and the sample was not chosen at random, this study used a One-Group Pretest-Posttest Design. The results of this study include: (1) The results of the initial test ability (pre-test) in the skills of writing explanatory texts for class VIII-5 students of SMP Negeri 2 Tapian Dolok before the Contextual Teaching and Learning (CTL) model is obtained an average value of 60. From the results of the pre-test showed that the students' ability to write explanatory texts had not yet reached the KKM target of 70. (2) The results of the final test (post-test) skills in writing explanatory texts for students of class VIII-5 SMP Negeri 2 Tapian Dolok after applying the Contextual model Teaching and Learning (CTL) obtained an average value of 70.38. From the post-test results obtained that the students' ability to write explanatory texts has reached the KKM target of 70. (3) The analysis that has been carried out and has been tested statistically that tcount is greater than ttable (3.38 > 2.042) causes H0 to be rejected and Ha received. Thus, it can be concluded that there is an effect of the Contextual Teaching and Learning (CTL) model on the skills of writing explanatory texts by grade VIII-5 students of SMP Negeri 2 Tapian Dolok.